Icelandic for foreign employees : a comparison of online and classroom training - Kristjana Björk Magnúsdóttir 1977- (2022)
Foreigners moving to Iceland and entering the labor market have increased significantly in the last few years. It is essential to learn the language in the country you live in to faster integrate into society. This experiment aims to answer if the Icelandic language learning outcome improves among the foreign employees having Icelandic classroom courses onsite straight after work, online Icelandic courses during working hours compared to having no Icelandic courses. The researcher created three groups of foreign employees. Two experimental groups, one received Icelandic language courses in classroom setting, the second one received Icelandic language courses online, and the control group received no Icelandic language course. All three groups were pre-and post-tested by doing a status assessment both in writing and by oral test in the Icelandic language. The participants also received a questionnaire with background questions at the beginning of the experiment. At the end of the experiment, the experimental groups received a training evaluation questionnaire. One of the policies in the organization is that all foreign employees should learn the Icelandic language. The result indicated that there was a significant difference in simple grammar score between classroom and online group but not in advanced grammar or oral. All the groups scores from the Icelandic language assessment improved except for the classroom group, the score decreased slightly in advanced grammar. Further implications are discussed, and suggestions for future research.